2017
DOI: 10.1002/2017gl074158
|View full text |Cite
|
Sign up to set email alerts
|

Seismic characteristics of supershear and sub‐Rayleigh earthquakes: Implication from simple cases

Abstract: Numerous investigations of supershear earthquakes make a conclusion that a supershear earthquake produces a seismic shock wave on the ground that may increase the resulting destruction. We investigate a supershear rupture promoted by the free surface and find out that although the seismic energy of a supershear earthquake can be transmitted further with large amplitudes, the peak slip velocity on a fault near the free surface is smaller than that caused by a subshear rupture earthquake. Our results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Similar Mach front attenuation in 3D setups was observed in Ref. [52] and reduced ground motion amplitude was shown to occur near the free-surface of simulated supershear earthquakes [53]. Additionally, once the finite-thickness of the plates is taken into account, our simulations show that the limiting rupture speed is larger than the plane-stress approximation.…”
Section: Discussionsupporting
confidence: 82%
“…Similar Mach front attenuation in 3D setups was observed in Ref. [52] and reduced ground motion amplitude was shown to occur near the free-surface of simulated supershear earthquakes [53]. Additionally, once the finite-thickness of the plates is taken into account, our simulations show that the limiting rupture speed is larger than the plane-stress approximation.…”
Section: Discussionsupporting
confidence: 82%
“…The surface traces of these faults are typically linear, continuous, and narrow, as evidenced by the optical satellite images [50], suggesting that stress-strength of the fault plane is mechanically homogeneous. What is more, supershear events tend to show a "quiet" aftershock potential, as revealed by both numerical simulations [51] and aftershock observations [49,52]. By contrast, aftershocks are likely to cluster on the secondary structures off the fault plane [52].…”
Section: An Early Supershear Rupture Of the Palu Earthquakementioning
confidence: 85%
“…Bouchon and Karabulut [52] also emphasized that friction is relatively uniform over the supershear segments deduced by the post-earthquake quiescence of the fault. As for the seismic hazard analysis of supershear ruptures, Zhang et al [51] reported that the supershear earthquake will bring in more strong shaking at large distance to the fault plane rather than intensive near-fault field ground motion, attributable to (1) the generation of S-wave Mach front, which can persist farther distance and (2) the seismic energy transmitted further with large amplitudes, which will definitely exacerbate the hazard [2,53,54].…”
Section: An Early Supershear Rupture Of the Palu Earthquakementioning
confidence: 99%
“…Although sustained supershear ruptures exist on both fault steps, the area with a sub‐Rayleigh rupture speed is larger on the extensional step with the 1.5 km step width (Hu, Xu, et al, ). Zhang et al () noticed that the near‐field ground motion associated with a free‐surface‐induced supershear rupture is smaller than that associated with a sub‐Rayleigh rupture. According to our study, sub‐Rayleigh ruptures may generate stronger horizontal PGV values close to strike‐slip fault segments.…”
Section: Numerical Resultsmentioning
confidence: 99%